Female entrepreneurship in East and South-East Asia : opportunities and challenges - Debroux, Philippe (Chandos Asian studies series., 2010)
This detailed study of female entrepreneurship in Asia examines the high economic growth that is increasingly driven by market-oriented economic reforms favouring entrepreneurship. There is a higher awareness by women of their political and socio-economic rights and recognition by society at large of social legitimacy of women pursuing business activities in their own right. This book assesses socio-cultural and economic factors influencing female entrepreneurship in Asia as well as the process and the tools and challenges that accompany it. Opportunity to acquire knowledge on the socio-economic roles played by women as entrepreneurs in the region Description and analysis of the issue in countries at different stages of economic development and with different socio-economic and cultural environmentA broad approach encompassing historical, political, sociological, economics and businesses-related aspects of female entrepreneurship.